Hubungan Pembelajaran Amtsilati dengan Pemahaman Nahwu Siswa MA Ma’arif NU Kencong - Ilmi Mufidah; Zainuri Zainuri (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
The purpose of this study is to determine the relationship between Amtsilati instruction and students’ understanding of Arabic grammar at MA Ma’arif NU Kencong. The phenomenon of students’ limited ability to apply Arabic grammatical rules to authentic texts is the primary rationale for this study. This study employs a quantitative, correlational design. Data were collected via a questionnaire distributed to students who had participated in the Amtsilati program, with rigorous validity and reliability testing. Given the non-normal distribution of the data, statistical analysis was conducted using the Spearman Rank correlation test. The main results of the study indicate a significant positive relationship between Amtsilati learning and students’ understanding of Arabic grammar, with a correlation coefficient of 0.606 and a significance level of 0.001. The main conclusion of this study is that the Amtsilati method, which is systematic, practical, and pattern-based, has been empirically proven to have a strong association with improving students’ linguistic competence. This finding confirms that practical methods can be an effective solution to the challenges of teaching Arabic grammar at the Madrasah Aliyah level.